FAKTOR-FAKTOR YANG MEMPENGARUHI EMESIS GRAVIDARUM PADA IBU HAMIL TRIMESTER 1 DI TPMB JAKARTA BARAT - Nopi Hendriani Hendriani; Sugiharti Sugiharti (Jurnal Ilmiah Kesehatan, 2024)
Objective: To determine the factors that influence Emesis Gravidarum in 1st Trimester Pregnant Women at TPMB Semanan, West Jakarta for the period 1 November 2023 - 31 January 2024. Methodology: This type of research is analytical descriptive and uses a cross sectional research design. Using total sampling, using data namely primary data, namely questionnaires and secondary data, namely data that already exists in the TPMB medical record Results: Statistical test results: obtained p value = 0.709, so it can be concluded that there is no relationship between age and the incidence of emesis gravidarum in pregnant women in the 1st trimester. Obtained a value of p = 0.067, it can be concluded that there is no relationship between education and the incidence of emesis gravidarum in pregnant women in the 1st trimester. And the p value obtained = 0.643 Conclusion: there is no relationship between work and the incidence of emesis gravidarum in pregnant women in the 1st trimester. This research shows that there is no relationship between age, education and employment and the incidence of emesis gravidarum in pregnant women in the 1st trimester at TPMB Semanan, West Jakarta for the period 1 November 2023 - 31 January 2024.